2023
DOI: 10.3390/nano13040700
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Molecules Detection via C2N Transistor-Based Sensor: First Principles Modeling

Abstract: Real-time detection of sugar molecules is critical for preventing and monitoring diabetes and for food quality evaluation. In this article, a field effect transistor (FET) based on two-dimensional nitrogenated holey graphene (C2N) was designed, developed, and tested to identify the sugar molecules including xylose, fructose, and glucose. Both density functional theory and non-equilibrium Green’s function (DFT + NEGF) were used to study the designed device. Several electronic characteristics were studied, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…48 In addition, the excellent structural characteristics of C 6 N 7 monolayers are analogous to the other C x N y monolayers [26][27][28][29][30][31][32][33] such as C 2 N, g-C 3 N 4 , C 3 N 2 , and C 7 N 6 monolayers, which have been demonstrated to be promising candidates for gas sensors to monitor toxic gases and VOCs. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] However, to our best knowledge, the adsorption behaviors and gas-sensing properties of VOCs on the C 6 N 7 monolayer for sensor exploration are still unknown, which motivates us to investigate the sensing performance and mechanism of the C 6 N 7 -based VOCs sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 In addition, the excellent structural characteristics of C 6 N 7 monolayers are analogous to the other C x N y monolayers [26][27][28][29][30][31][32][33] such as C 2 N, g-C 3 N 4 , C 3 N 2 , and C 7 N 6 monolayers, which have been demonstrated to be promising candidates for gas sensors to monitor toxic gases and VOCs. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] However, to our best knowledge, the adsorption behaviors and gas-sensing properties of VOCs on the C 6 N 7 monolayer for sensor exploration are still unknown, which motivates us to investigate the sensing performance and mechanism of the C 6 N 7 -based VOCs sensors.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, the increasing of the N-to-C ration in carbon nitrides generates novel electronic features and chemical/physical properties such as the tunable nanopore size and band gap and adjustable conductivity, which are promising for key applications. In this context, the CN-based monolayers have been extensively used in gas sensing and exhibited high sensitivity and selectivity towards toxic gas and VOCs such as C 2 N, 34–37 C 3 N, 38–41 CN, 42–44 C 3 N 2 , 45 C 7 N 6 , 46,47 C 6 N 7 , 48 g-C 3 N 4 , 49,50 and BC 6 N 51,52 monolayers, which further motivates people's enthusiasm to exploit new C x N y structures with high-performance gas sensing. In particular for the sensing of VOCs, Agrawal et al 39 has confirmed that the C 3 N monolayer has relatively high sensing performance for acetone and isopropanol detection, while Ma et al 40 has predicted that the Cu-doped C 3 N monolayer has promising potential for optical VOCs sensors.…”
Section: Introductionmentioning
confidence: 99%